Ectoparasites Identification Of Indigo Red Fish (Oreochromis nilotica) Cultivated In The Center Of The Fish Fry (BBI) Ranomeeto - Dedi Sunarto (Journal of Biological Science and Education, 2019)
Diseases caused by parasitic groups received less serious attention from the farmers because the disease is chronic morbidity and mortality rates and small. However, if observed further, parasitic diseases can lead to secondary infection by bacteria, viruses, and fungi that can cause death and high losses. This study aims to identify the types of ectoparasites red tilapia (Oreochromis nilotica) at Fish Seed Center (BBI) Ranomeeto, South Konawe. This type of method used was observational and sampling was done by using purposive sampling, ie taking into account the characteristics / criteria sample has been determined. These samples included 30 individuals of red tilapia fish taken from BBI Ranomeeto South Konawe. Observations ectoparasites done in Laboratory of Department of Biology at Halu Oleo University . From some of the samples examined Trichodina sp. found to infect the gills, skin and fins. Ichthyophthyrius sp. found on the skin. The dominant type of ectoparasites found is kind Trichodina sp. with a prevalence of 60% and Ichthyophthyrius sp. with a prevalence of 46.67%.   Keywords: Red Tilapia, Ectoparasites, and Organ Infections